The Influence of the Motor Vehicle Tax Reduction Program and Exemption of Transfer of Title Fees on Taxpayer Compliance in the North Jakarta Region - Atikah, Atikah; Abdillah, Abdillah; Irawan, Ade (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The aim of this research is to determine the influence of hotel tax revenues on the level of economic growth in DKI Jakarta Province, the influence of motor vehicle tax revenues on the level of economic growth in DKI Jakarta Province, and the influence of hotel tax revenues and motor vehicle taxes together (simultaneously) on the level of economic growth in DKI Jakarta Province. This research uses a quantitative descriptive method with data collection techniques through distributing questionnaires. This research uses the realization of Original Regional Income revenue for the DKI Jakarta Province during 2012-2022, using multiple linear regression data analysis techniques. The results of this research show that there is. There is an influence of hotel tax revenue on the level of economic growth, there is an influence of motor vehicle tax revenue on the level of economic growth and there is an influence of hotel tax revenue and motor vehicle tax together (simultaneously) on the level of economic growth in DKI Jakarta Province. It is hoped that the results of this research will contribute to further research.